2019
DOI: 10.1016/j.fbp.2018.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic surface modifications of stainless steel targeting dairy fouling mitigation and bacterial adhesion

Abstract: This work aims at presenting and comparing the antifouling and antibacterial behaviour of three biomimetic surfaces targeting dairy fouling reduction, namely atmospheric plasmasprayed silane-based thin films, lubricated slippery surfaces and femtosecond laser textured lotus-like surfaces. Fouling tests were conducted on a pilot-scale pasteurization plant fed with a model whey protein and calcium foulant solution and tested samples were placed in isothermal holding-like conditions. Detailed characterizations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Initial bacterial adsorption onto the surface due to intermolecular forces, such as vdW forces or electrostatic attraction, and subsequent fixing of the bacteria onto the surface by biofilm formation is effectively reduced. Any bacterial cells that do come into relatively close proximity of the liquid–solid interface are likely carried away by external forces or random Brownian motion before they can start to form a biofilm and proliferate (Ayazi et al., 2019; Crick et al., 2011; Fadeeva et al., 2011; Manoj et al., 2020; Oh, Lu, et al., 2015; Oh, Kohli et al., 2016; Zouaghi et al, 2019). It has been noted by several authors that the extent of hydrophilic bacteria adhesion onto surfaces generally decreases with increasing surface hydrophobicity or decreasing surface energy (Absolom et al, 1983; Cunliffe et al, 1999; Parreira et al, 2011).…”
Section: Superhydrophobic Antifouling (Anticontact) Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial bacterial adsorption onto the surface due to intermolecular forces, such as vdW forces or electrostatic attraction, and subsequent fixing of the bacteria onto the surface by biofilm formation is effectively reduced. Any bacterial cells that do come into relatively close proximity of the liquid–solid interface are likely carried away by external forces or random Brownian motion before they can start to form a biofilm and proliferate (Ayazi et al., 2019; Crick et al., 2011; Fadeeva et al., 2011; Manoj et al., 2020; Oh, Lu, et al., 2015; Oh, Kohli et al., 2016; Zouaghi et al, 2019). It has been noted by several authors that the extent of hydrophilic bacteria adhesion onto surfaces generally decreases with increasing surface hydrophobicity or decreasing surface energy (Absolom et al, 1983; Cunliffe et al, 1999; Parreira et al, 2011).…”
Section: Superhydrophobic Antifouling (Anticontact) Surfacesmentioning
confidence: 99%
“…The three key requirements for successful SLIPS fabrication are that the solid used for immobilization has a higher affinity for the immobilized fluid than it does for water, that the solid is textured to increase its effective contact area with the immobilized fluid, and that the immobilized lubricating fluid is immiscible with water (Epstein et al., 2020). Slips have been successfully created by anodizing aluminum (Wang, Zhang, et al., 2015), laser‐etching stainless steel (Zouaghi et al., 2019), or depositing multiwalled carbon nanotubes (MWCNTs) onto stainless steel (Rungraeng et al., 2015) to create roughened substrate surfaces. Porous polytetrafluoroethylene film has also been utilized (Epstein et al., 2020).…”
Section: Other Antifouling Surface Modificationsmentioning
confidence: 99%
“…Ivanova et al reported that the nano-sized structures on the wings of cicadas and dragonflies exhibit antibacterial activity (Ivanova et al 2012 , 2013 ; Pogodin et al 2013 ). Following this report, various artificial nanostructures with antibacterial and sterilization properties have been actively researched (Zouaghi et al 2019 ; Hasan et al 2020 ; Mann et al 2014 ). Micro-sized patterns also show antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…These include the well-studied hydrophobic self-cleaning properties of certain plant species, such as the “lotus effect” as observed in Nelumbo nucifera (whose mechanisms are elucidated and effects artificially reproduced in [ 25 , 26 , 27 ]). Some of these approaches have made it out of the laboratory and into broader technical applications, including some interesting recent patents [ 28 ] and applications [ 29 ]. Of course, these strategies have drawbacks, and there are undoubtedly technical challenges to be overcome in many applications—for example, Flemming points out that the lotus effect, despite its aquatic origins, has not found widespread commercial application on surfaces submerged in water, as the methods to date are based on hydrophobicity requiring the presence of both water and gas phases (a liquid–gas interface), which is difficult to maintain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%